2021
DOI: 10.3390/atmos12091192
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Low-Cost Personal Monitoring for Exposure to PM2.5 among Asthmatic Children: Opportunities and Challenges

Abstract: This study aims to evaluate the accuracy and effectiveness of real-time personal monitoring of exposure to PM concentrations using low-cost sensors, in comparison to conventional data collection method based on fixed stations. PM2.5 data were measured every 5 min using a low-cost sensor attached to a bag carried by 47 asthmatic children living in the Seoul Metropolitan area between November 2019 and March 2020, along with the real-time GPS location, temperature, and humidity. The mobile sensor data were then m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Their study demonstrates the successful use of GPS-attached Pocket PM 2.5 sensors for mobile sensing and continuous measurement. In Seoul, Korea, the personal PM 2.5 exposures of 47 asthmatic children were investigated with an emphasis on comparing the accuracy and effectiveness of the real-time personal monitoring using LCPMS (PICO, model: PMM-130) to those obtained from monitoring stations [103]. They found that average PM 2.5 concentrations measured by personal monitoring were lower than those measured by the monitoring stations, especially when the individuals were indoors, at night, and much further away from the monitoring station.…”
Section: The 24-h Personal Pm 25 Exposurementioning
confidence: 99%
“…Their study demonstrates the successful use of GPS-attached Pocket PM 2.5 sensors for mobile sensing and continuous measurement. In Seoul, Korea, the personal PM 2.5 exposures of 47 asthmatic children were investigated with an emphasis on comparing the accuracy and effectiveness of the real-time personal monitoring using LCPMS (PICO, model: PMM-130) to those obtained from monitoring stations [103]. They found that average PM 2.5 concentrations measured by personal monitoring were lower than those measured by the monitoring stations, especially when the individuals were indoors, at night, and much further away from the monitoring station.…”
Section: The 24-h Personal Pm 25 Exposurementioning
confidence: 99%
“…For these aims, we compared the routine ambient air quality monitoring data provided by the Korean Ministry of Environment titled "Air Korea" with new sensor-based air monitoring data from the Korea Testing & Research Institute (KTR). For the Air Korea data, PM 2.5 concentrations were measured by the standard β-ray measurement method at 5 min intervals and then aggregated into hourly averages through statistical processing before being stored in a database [18]. This government-grade air monitoring station provides relatively accurate data but is expensive to run due to high installation and maintenance costs [19].…”
mentioning
confidence: 99%